Schistosoma haematobium infection and environmental factors in Southwestern Tanzania: A cross-sectional, population-based study. - Kirsi M Manz; Inge Kroidl; Petra Clowes; Martina Gerhardt; Wilbrod Nyembe; Lucas Maganga; Weston Assisya; Nyanda E Ntinginya; Ursula Berger; Michael Hoelscher; Elmar Saathoff (Public Library of Science (PLoS), 2020)
Schistosomiasis is a leading cause of morbidity in Africa. Understanding the disease ecology and environmental factors that influence its distribution is important to guide control efforts. Geographic information systems have increasingly been used in the field of schistosomiasis environmental epidemiology. This study reports prevalences of Schistosoma haematobium infection and uses remotely sensed and questionnaire data from over 17000 participants to identify environmental and socio-demographic factors that are associated with this parasitic infection. Data regarding socio-demographic status and S. haematobium infection were obtained between May 2006 and May 2007 from 17280 participants (53% females, median age = 17 years) in the Mbeya Region, Tanzania. Combined with remotely sensed environmental data (vegetation cover, altitude, rainfall etc.) this data was analyzed to identify environmental and socio-demographic factors associated with S. haematobium infection, using mixed effects logistic regression and geostatistical modelling. The overall prevalence of S. haematobium infection was 5.3% (95% confidence interval (CI): 5.0-5.6%). Multivariable analysis revealed increased odds of infection for school-aged children (5-15 years, odds ratio (OR) = 7.8, CI: 5.9-10.4) and the age groups 15-25 and 25-35 years (15-25 years: OR = 5.8, CI: 4.3-8.0, 25-35 years: OR = 1.6, CI: 1.1-2.4) compared to persons above 35 years of age, for increasing distance to water courses (OR = 1.4, CI: 1.2-1.6 per km) and for proximity to Lake Nyasa (<1 km, OR = 4.5, CI: 1.8-11.4; 1-2 km, OR = 3.5, CI: 1.7-7.5; 2-4 km; OR = 3.3, CI: 1.7-6.6), when compared to distances >4 km. Odds of infection decreased with higher altitude (OR = 0.7, CI: 0.6-0.8 per 100 m increase) and with increasing enhanced vegetation index EVI (OR = 0.2, CI: 0.1-0.4 per 0.1 units). When additionally adjusting for spatial correlation population density became a significant predictor of schistosomiasis infection (OR = 1.3, CI: 1.1-1.5 per 1000 persons/km2) and altitude turned non-significant. We found highly focal geographical patterns of S. haematobium infection in Mbeya Region in Southwestern Tanzania. Despite low overall prevalence our spatially heterogeneous results show that some of the study sites suffer from a considerable burden of S. haematobium infection, which is related to various socio-demographic and environmental factors. Our results could help to design more effective control strategies in the future, especially targeting school-aged children living in low altitude sites and/or crowded areas as the persons at highest need for preventive chemotherapy.